The Choreography of Gender in Traditional Vietnamese Music - Thuy, Nguyen Thanh (Sweden Lund University, 2019)
This Ph.D. project in artistic research is concerned with the function of gesture in traditional Vietnamese music. Building on gender analysis of musical performance in TV shows, and further on autoethnographic inquiry throughout the artistic projects, the artistic output articulates a critical understanding of these practices. The aims of the project are to investigate the social function and meaning of musical gesture in traditional Vietnamese music, and to develop artistic responses that articulate an individual voice. The research questions that emerge from these conceptual and artistic aims are:1. What gender conventions can gesture analysis of musical performance unveil?2. In what ways can music created through the choreographic structuring of movement revealand question gender conventions in musical performance?3. How can my performance, in intercultural and interdisciplinary artistic collaborations,challenge current gender norms and instigate change in practices of traditional Vietnamese music?The method and design of this Ph.D. project builds on qualitative analysis of gesture in musical performance, with particular emphasis on employing a gender perspective in this analysis. In the artistic work, analysis of gesture has constituted a point of departure for the creation of a series of intermedia works that seek to develop methods that combine the practices of choreography and musical composition. Intercultural collaboration has provided particular challenges and possibilities in the development of each of these works. The results of the artistic work are published online in The Research Catalogue.The outcomes of the project outline how gendered gesture is taught in higher music education in Vietnam, and taken together with the historical overview of how nationalism and communism has shaped the country, that this teaching has an immediate relation to nation branding. The teaching of traditional music is equally related to the commercialised views of women as it is grounded in the preservation of tradition. Further, the development of a practice of composing music using gestural-sonorous objects as material became the central artistic method throughout this Ph.D. project. It has offered novel possibilities of approaching gestural materials and creating new choreographies and music based on a critical approach to the image of women in popular media. The results finally suggest that intercultural and inter-disciplinary artistic practice can propose social change, and provide counter images of traditionally gendered behaviour.
Doctoral Dissertation by due permission of the Faculty of Fine and Performing Arts, Lund University, Sweden. To be defended at Inter Arts Center, Malmö, november 2019
Keywords: Folk music; Gender; Vietnam